The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1998
DOI: 10.1007/s004670050538
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of immunosuppressants in steroid-dependent nephrotic syndrome

Abstract: In order to elucidate long-term effects of immunosuppressants, we studied 60 children with steroid-dependent nephrotic syndrome who were treated with three immunosuppressants: cyclophosphamide (n=34), chlorambucil (n=11), and cyclosporin A (n=15). Each relapse before and after the administration of immunosuppressants was evaluated longitudinally in terms of the relapse-free period and the maintenance dose of prednisolone required. The median follow-up period after immunosuppressants was 5.2 years (range 0.5-20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 17 publications
0
18
1
Order By: Relevance
“…It resulted in cumulative relapse free survival of 78.3% at the last follow up. Some earlier reports also suggested a superior effect of CHL over other alkylating agents [18,25,26]. But the straightforward comparison of the domestic and international treatment regimes is relative since in our patients the dosage of CHL was generally higher than standard one.…”
Section: Discussioncontrasting
confidence: 46%
See 2 more Smart Citations
“…It resulted in cumulative relapse free survival of 78.3% at the last follow up. Some earlier reports also suggested a superior effect of CHL over other alkylating agents [18,25,26]. But the straightforward comparison of the domestic and international treatment regimes is relative since in our patients the dosage of CHL was generally higher than standard one.…”
Section: Discussioncontrasting
confidence: 46%
“…under the SSNS are not presented in the Western literature. The data concerning the use of CHL are nowadays rarely presented being usually reported in the earlier studies [18,25,26].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In addition, the variable responses to steroids among MCNS patients do not have an apparent attribution to the characteristics of the patients’ glucocorticoid receptors [5]. Furthermore, children with steroid-dependent nephrotic syndrome also responded variably to immunosuppressive and immunostimulating drugs [6,7]. These findings suggest that steroid dependence does not solely rely on the immune mechanisms.…”
Section: Introductionmentioning
confidence: 83%
“…To date, a large number of studies have indicated that podocyte injury, loss and dysfunction have an important role in pathologies including focal segmental glomerulosclerosis and membranous nephropathy (3)(4)(5). Immunosuppressants (e.g., steroids or cyclosporine A) have been used based on anecdotal evidence to treat NS (6). Unless a contraindication exists, glucocorticoids (GC) continue to be the first-line therapy (7).…”
Section: Introductionmentioning
confidence: 99%